2013
DOI: 10.1016/j.pain.2013.02.006
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional examination of the relationships between caregiver proximal soothing and infant pain over the first year of life

Abstract: Although previous research has examined the relationships between caregiver proximal soothing and infant pain, there is a paucity of work taking infant age into account, despite the steep developmental trajectory that occurs across the infancy period. Moreover, no studies have differentially examined the relationships between caregiver proximal soothing and initial infant pain reactivity and pain regulation. This study examined how much variance in pain reactivity and pain regulation was accounted for by careg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 36 publications
2
29
0
Order By: Relevance
“…A similar pattern was found for caregiver coping-and distress-promoting behaviors in study 2. In line with previous research, 1,17,25 children's pain strongly predicts subsequent children's pain prospectively. An integration of these findings with a focus on clinical implications will be presented in our conclusion.…”
Section: Study 1: the Relationships Between Children's Coping Responssupporting
confidence: 90%
See 2 more Smart Citations
“…A similar pattern was found for caregiver coping-and distress-promoting behaviors in study 2. In line with previous research, 1,17,25 children's pain strongly predicts subsequent children's pain prospectively. An integration of these findings with a focus on clinical implications will be presented in our conclusion.…”
Section: Study 1: the Relationships Between Children's Coping Responssupporting
confidence: 90%
“…In terms of entering child distress behaviors from the directly preceding time epoch into the models, this choice was made because a critical assumption in creating the path models was that young children's pain responding during painful procedures has been established to predict subsequent pain responding to that procedure. 1,17,25 Thus, all path models included a predictor variable of preschooler's pain-related distress from the closest time point preceding each dependent variable of interest. To parallel this, the same was done with both coping-promoting and distresspromoting caregiver variables.…”
Section: Data Analysis 241 Study 1: the Relationships Between Presmentioning
confidence: 99%
See 1 more Smart Citation
“…The first infant waves of the cohort were naturalistic observations of infants and their parents at their 2, 4, 6 and 12 month immunizations. Among the findings from this longitudinal study, it was found that commonly occurring parent pain management strategies from the literature (e.g., rocking, proximal soothing, verbal reassurance) accounted for statistically significant yet minimal amounts of variance in infant pain responding (ranging from 2 to 13%) [5][6][7]. It was shown that as children aged over the first year of life, parent strategies accounted for increasing variance in observed childhood pain-related distress.…”
Section: Parent-led Interventions Have Minimal Effect On Infant Pain mentioning
confidence: 73%
“…were included in the current analyses, as they have been shown to have the strongest relationship with infant pain-related distress [6,22]. The three caregiver behaviours were coded as present (1) or absent (0) for five-second epochs during the following three 60-second periods: (1) the oneminute period prior to the needle, (2) the one-minute period following the last needle, and (3) the two-minute period following the last needle.…”
Section: Measure Of Adult and Infant Soothing And Distress (Maisd) Imentioning
confidence: 99%